Public-Private Partnerships in Developing Countries : The Emerging Evidence-based Critique - Leigland, James (Published by Oxford University Press on behalf of the World Bank, 2019)
Advocates of public-private partnerships (PPPs) for infrastructure services in developing countries have long battled criticism of these arrangements by civil society groups. The view among PPP advocates generally has been that these criticisms are mostly ideological polemics thatmix opinion with selected but often misinterpreted facts. But over the last two decades, as the experience with PPPs has increased in both developed and developing countries, a different kind of critique has emerged, one that is based on non-ideological empirical research, and is sometimes expressed by PPP advocates. These studies often focus on individual aspects of PPPs, and usually do not claim to be “PPP evaluations” or express opinions on the overall value of PPPs. Taken together, a powerful, evidence-based critique of PPPs is emerging, but one that ismoremeasured thanmuch of the criticism of the last two decades. This new critique recognizes many cases in which PPPs have not been successful, but also some situations in which PPPs can generate value for money. Because of its critical tone, some of this research is now regularly cited by the civil society critics of PPPs, giving their arguments more weight than was the case a decade ago. This paper attempts to summarize some of the most compelling examples of this kind of emerging critique, and uses the summary to assess the practicality of the G20’s recent advocacy of large, “transformational” PPPs as tools for dealing effectively with infrastructure challenges in low-income countries.